Shifting Social Preferences towards Moral Prejudices in a Process of Resource Allocation Decision Making - Kovalenko, Alla; Головіна, Альбіна (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
This paper presents an analysis of the main theories and results of experimental research in the context of the shifting social preferences towards moral prejudices in a process of resource allocation decision making. Researchers of game theory have found that three motives are included in the decision-making process about resource allocation: social preferences, moral prejudices, and self-interest. Personal interests and moral prejudices are strong predictors in the model of predicting people’s social orientations. Moral prejudices, being the distortions created by self-interest, can strongly influence people’s social preferences, and even change them to the opposite. As a result, an asymmetric relationship is established between personal interest and moral prejudices in the decision-making process about resource allocation. When moral prejudices become an obstacle to achieving a goal, a person unconsciously distorts the information so that it justifies its actions. These distortions can be manifested in the avoidance of information that interferes with personal interests, the selective selection of information, and even recourse to opposing moral principles. In the long run, all this is expressed in the change of a person’s social orientation from altruistic to selfish. These changes in people’s social preferences are confirmed by the results of numerous experiments not only in social psychology, but also in social neuropsychology and neuroeconomics. The way to overcome these distortions is to have a clear understanding of the limits of personal interests and an understanding of one’s own motives in decisions about resource allocation.